Accuracy of Intraoperative Computed Tomography Assisted Dorsal Instrumentation in Spinal Revision Surgery - Bertram, Ulf; Clusmann, Hans; Geiger, Matthias Florian; Riabikin, Alexander; Mueller, Christian-Andreas; Blume, Christian (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Purpose Instrumentation in spinal revision surgery is considered challenging. Altered or missing anatomical landmarks hinder the surgeons' intraoperative orientation. In recent history, the importance of navigated approaches to spinal screw placement is constantly increasing. A growing number of medical centers have introduced intraoperative CT (iCT) navigation as a new clinical standard. In this study, we compare the accuracy of dorsal iCT-navigated instrumentation in revision surgery versus primary interventions.Methods Between September 2017 and January 2019, we prospectively analyzed a consecutive series of dorsal instrumentation using iCT. Patients with previous operative interventions in the relevant spinal segments were included in the revision group and compared with a previously assessed group of primary interventions (nonrevision group). Each screw was assessed individually by an independent observer, making use of a modified Gertzbein and Robbins classification.Results In this period, 39 patients were treated in the revision group with a total amount of 269 implanted screws. We achieved an overall accuracy of 95.91% compared with 95.12% in the nonrevision group (46 patients, 287 screws). We found no significant difference in accuracy between the two groups or any anatomical region of the spine.Conclusion In summary, iCT-navigated screw placement yields a good accuracy in spinal revision surgery, without significant difference to primary interventions.
Keywords: revision spine surgery; navigation; intraoperative computed tomography; 3D imaging; accuracy